2012
DOI: 10.1037/a0028824
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of temporary hippocampal lesions on single and dual context versions of the olfactory sequence memory task.

Abstract: In recent years, many animal models of memory have focused on one or more of the various components of episodic memory. For example, the odor sequence memory task requires subjects to remember individual items and events (the odors) and the temporal aspects of the experience (the sequence of odor presentation). The well-known spatial context coding function of the hippocampus, as exemplified by place cell firing, may reflect the ‘where’ component of episodic memory. In the present study, we added a contextual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Finally, using an incidental recognition task (visual paired-comparison or object/context-VPC), Bachevalier and colleagues (Bachevalier et al 2015) demonstrated a lack of novelty preference in monkeys with selective hippocampal lesions sustained in adulthood when a familiar object was presented over a new background. Similar findings have also been reported in humans, rabbits and rodents (Burgess et al 2001; Freeman et al 1997; Kennedy & Shapiro 2004; Kim & Fanselow 1992; Kim et al 2012; Mayes et al 1992; Smith & Mizumori 2006; Penick & Solomon 1991; Phillips & LeDoux 1992; Rudy et al 2002; Sill & Smith 2012; Pascalis et al 2009; Spiers et al 2001).…”
Section: Introductionsupporting
confidence: 88%
“…Finally, using an incidental recognition task (visual paired-comparison or object/context-VPC), Bachevalier and colleagues (Bachevalier et al 2015) demonstrated a lack of novelty preference in monkeys with selective hippocampal lesions sustained in adulthood when a familiar object was presented over a new background. Similar findings have also been reported in humans, rabbits and rodents (Burgess et al 2001; Freeman et al 1997; Kennedy & Shapiro 2004; Kim & Fanselow 1992; Kim et al 2012; Mayes et al 1992; Smith & Mizumori 2006; Penick & Solomon 1991; Phillips & LeDoux 1992; Rudy et al 2002; Sill & Smith 2012; Pascalis et al 2009; Spiers et al 2001).…”
Section: Introductionsupporting
confidence: 88%
“…This is consistent with previous reports showing that ventral hippocampus has a role in processing nonspatial information (Bannerman et al, 2002; Kjelstrup et al, 2002) and is less critical for spatial learning and memory than dorsal hippocampus (de Hoz et al, 2003; Moser et al, 1993; Moser and Moser, 1998). There are a number of studies that have implicated the hippocampus in processing contextual information (Mumby et al, 2002a; Maren, 2008; Rudy, 2009; Sill and Smith, 2012). Our current data would suggest that these effects are most likely mediated through the LEC, DG, and ventral hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…A review of these studies is beyond the scope of this article but a number of findings are particularly relevant to the data presented here. The hippocampus has been shown to be necessary for complex associations of stimuli that may parallel OPC associations (Good et al, 2007 ; Sill and Smith, 2012 ). However, the hippocampus has also been implicated in associations that are possibly more basic (paralleling the OP/OC recognition tasks used here) such as learning odor-context associations for reward (Komorowski et al, 2009 ; Morris et al, 2013 ), object-context associations (Mumby, 2002 ; Piterkin et al, 2008 ) learning cue-context associations (Good et al, 1998 ; Honey and Good, 2000 ; Ainge et al, 2012 ), learning new odor-place (Gilbert and Kesner, 2002 ; Goodrich-Hunsaker et al, 2009 ) and object-place associations (Gaffan and Harrison, 1989 ; Parkinson et al, 1988 ; Sziklas et al, 1998 ; Bussey et al, 2000 ; Gilbert and Kesner, 2002 ; Crane and Milner, 2005 ; Lee and Solivan, 2010 ; Barker and Warburton, 2011 ) although see (Malkova and Mishkin, 2003 ).…”
Section: Discussionmentioning
confidence: 99%